PENERAPAN MODEL MASTERY LEARNING BERBANTUAN LKPD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK DI KELAS VIII.3 SMP NEGERI 4 KOTA BENGKULU - novelia, rika; rahimah, dewi; syukur, muhammad fachruddin (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2017)
AbstractThis research aims to find out how to apply the Mastery Learning model assisted LKPD can improve the activity and student’s learning outcomes. This research was a classroom action research with data collection technique through observation sheet of student’s activity and test of student’s learning result. The subjects of this research were Class VIII.3 SMP Negeri 4 Kota Bengkulu academic year 2016/2017 which amounted to 35 students. The results showed the application of Mastery Learning model assisted LKPD can improve the students learning outcomes by linking the learning material with the daily life, motivating to ask questions, as well as guide in doing the exercise questions. Improved learning outcomes can be seen from the average value of students in the cycle I to cycle III that is in the cycle I 66,21 with the percentage of learning completeness that is 42.86%; in the cycle II 79,14 with the percentage of learning completeness that is 68.57%; and in the cycle III 89,50 with the percentage of learning completeness that is 91.43%.Keywords: Learning Outcomes, LKPD, Mastery Learning.